2020
DOI: 10.1186/s12911-020-01268-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of incident myocardial infarction using machine learning applied to harmonized electronic health record data

Abstract: Background With cardiovascular disease increasing, substantial research has focused on the development of prediction tools. We compare deep learning and machine learning models to a baseline logistic regression using only ‘known’ risk factors in predicting incident myocardial infarction (MI) from harmonized EHR data. Methods Large-scale case-control study with outcome of 6-month incident MI, conducted using the top 800, from an initial 52 k procedures, diagnoses, and medications within the UCHealth system, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
6
20
0
Order By: Relevance
“…Although these approaches tended to improve the prediction accuracy as assessed by the F1 score and other measures of classification, they resulted in models that tended to predict a rhythm-control strategy more often than one was actually used, suggesting that they were overfitting the data. This result is consistent with previous work using machine learning to predict rare outcomes from EHR data by our team, including the prediction of AF itself [ 33 ] and myocardial infarction [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although these approaches tended to improve the prediction accuracy as assessed by the F1 score and other measures of classification, they resulted in models that tended to predict a rhythm-control strategy more often than one was actually used, suggesting that they were overfitting the data. This result is consistent with previous work using machine learning to predict rare outcomes from EHR data by our team, including the prediction of AF itself [ 33 ] and myocardial infarction [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Second, we found that only neural networks could provide the computational power to produce accurate prediction models with big data inputs; none of the other approaches provided an AUC over 0.5 (F1 score>0.0) when applied to big data inputs. This result is also similar to previous findings with the application of machine learning to EHR data [ 32 , 33 ] and suggests the power of deep learning over standard methods, which has been demonstrated widely across a range of applications [ 44 - 46 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…While DL models often result in accurate predictions, it is hard to interpret and rationalize the results. Moreover, studies show that for harmonized EHRs data, a DL model did not show superior benefits compared with traditional methods [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is harmonizing EHR under standard data models like Observational Medical Outcomes Partnership (OMOP) and Fast Healthcare Interoperability Resources (FHIR). These data models put well-known limitations on granularity of EHR and cannot handle variations in the data patterns themselves 14,15 . These challenges hinder wide-spread adoption of EHR-based ML/DL models across multiple institutions.…”
Section: Introductionmentioning
confidence: 99%